Parity is Related to Anemia in Pregnant Women in the Coastal Area - Askrening, Askrening; Wiralis, Wiralis; Mangun, Mardiani; Suwarni, Suwarni (Poltekkes Kemenkes Palu, 2025)
Maternal mortality is still a serious problem in Indonesia. One of the causes is anemia in pregnant women. Anemia in pregnant women is very influential not only on the mother, but on the fetus, and the process of childbirth. The purpose of the study was to analyze the relationship between parity, gestational age and the incidence of anemia in pregnant women in coastal areas in Soropia sub-district, Konawe Regency Design Method of analytical observational research with cross sectional design, sample selection with purposive. The population of all pregnant women in Soroia sub-district. Large sample of 38 respondents, variables of parity study, gestational age and anemia. Questionnaires and Hb check tools were used to measure the variables of parity, gestational age and Hb respondents. Chi-square statistical analysis with α = 0.05. The results showed a significant relationship between parity and anemia in pregnant women (p = 0.036). Pregnant women in the 2nd and 3rd trimesters were more likely to have anemia than pregnant women in the 1st trimester, although the relationship was not significant (p = 0.12). Conclusion. The more parity many tend to be anemic and the closer to birth the Hb decreases.